Genetic Polymorphisms of Infectious Diseases in Case-Control Studies. Issue 3 (21st May 2013) - Pacheco, Antonio G.; Moraes, Milton O.
Abstract : In the past decade, genetic epidemiological analyses in infectious diseases have increased drastically since the publication of human genome and all the subsequent projects analyzing human diversity at molecular level. The great majority of studies use classical epidemiological designs applied to genetic data, and more than 80% of published studies use population-based case-control designs with widely spread genetic markers in human genome, like short tandem repeats (STR) or single nucleotide polymorphisms (SNP), in genes chosen by their physiological association with the disease (candidate genes). Even though genetic data is less prone to several bias issues inherent to case-control studies, some care has to be taken when designing, performing, analyzing and interpreting results from such studies. Here we discuss some basic concepts of genetics and epidemiology as a departure to evaluate and review every step that should be followed to design, conduct, analyze, interpret and present data from those studies, using particularities of infectious diseases, especially leprosy and tuberculosis as models.